WSP’s Engagement in the Rural Sanitation Sector in India : Successes and Challenges - Brocklehurst, Clarissa; Mead, Simon; Verhagen, Joep (World Bank, Washington, DC, 2016)
In October 2014, the Water and Sanitation Program (WSP) initiated a study to document its engagement in the rural sanitation sector in India between 2002 and 2013. The intent was to learn from achievements, challenges, and lessons from the past as the Water Global Practice of the World Bank and other stakeholders intensify efforts to address the huge challenge of realizing the Government of India’s goal of universal rural sanitation in India by 2019. The study covered a cross-section of eight states in which WSP has worked as well as an examination of activities at the national level. The primary source of information was 138 structured interviews with key informants including Indian Government officials at all levels: (a) representatives of development agencies and civil society organisations; and (b) current and former WSP staff. The key findings were as follows: (i) Creating champions is a key determinant of success, and new, more cost-effective, and scalable approaches must be developed; (ii) Effective ways must be found to increase awareness and willingness to act among senior decision makers at state level; (iii) New implementation models must be developed that support the work of state governments to roll out sanitation at scale, and state governments must be supported to institutionalize them; and (iv) Mechanisms must be found to support decentralized, large-scale sector capacity building. These insights will be used to develop future interventions that will further accelerate change and help achieve the goal of universal rural sanitation in India